2017
DOI: 10.15421/021778
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific response to acute hyperthermal stress of Haworthia (Asphodelaceae) plants

Abstract: An increase in environmental temperature is one of the most common stress factors for plant organisms. The study of the plants’ adaptation to stress factors remains extremely important and relevant. This article presents the results of a acute short-term influence of hyperthermia on species of two subgenera of the genus Haworthia Duval. We investigated the different levels of antioxidant protection and damage degree of the members of two subgenera of the genus Haworthia at the biochemical level, measuring the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 29 publications
(37 reference statements)
4
3
0
Order By: Relevance
“…Absence an additional epidermal protection may be accompanied by the stress influence of high temperature on internal leaf structures. Similar results were observed on haworthias and representatives of the Cactaceae family [15,16,37] and rhododendrons, where the least heat-resistant species were those which had the thinnest leaves, thinner outside cell walls and larger epidermal cell surface areas [38]. In C. muscosa, hyperthermia caused stress already at 40 °C, and at 50 °C the MDA content was tripled.…”
Section: Methodssupporting
confidence: 69%
See 4 more Smart Citations
“…Absence an additional epidermal protection may be accompanied by the stress influence of high temperature on internal leaf structures. Similar results were observed on haworthias and representatives of the Cactaceae family [15,16,37] and rhododendrons, where the least heat-resistant species were those which had the thinnest leaves, thinner outside cell walls and larger epidermal cell surface areas [38]. In C. muscosa, hyperthermia caused stress already at 40 °C, and at 50 °C the MDA content was tripled.…”
Section: Methodssupporting
confidence: 69%
“…Increase of peroxidase activity in response to high temperature treatment was also confirmed by other researchers [33,34]. At the same time, other species displayed somewhat different results as for the role of peroxidase in the antioxidant response to high temperature: peroxidase activity increased or stayed the same for rhododendrons and haworthias [15]; activity increased, decreased or stayed the same [16,34]. Anatomical structure studies has shown that representatives of С. perfoliata var.…”
Section: Methodssupporting
confidence: 62%
See 3 more Smart Citations